Efeitos do pré-condicionamento isquêmico remoto sobre a dor aguda pós-operatória em colecistectomia convencional - Pereira, Francisco Elano Carvalho (2014)
The remote ischemic preconditioning (PCIR) results from a series of short nonlethal periods of ischemia interspersed by periods of reperfusion in distant tissues. Experimental and clinical studies have been published in recent years demonstrating the relationship between analgesia and ischemic preconditioning. Promoting PCIR with limb ischemia is feasible in clinical models. The aim of this study was to evaluate the effect of remote ischemic preconditioning on the intensity and quality of acute postoperative analgesia and production of inflammatory mediators in conventional cholecystectomy. Prospectively 20 patients were randomly divided into two groups. One group was subjected to an episode of ischemia in the lower limb before surgery. It was evaluated: the consumption of opioid analgesics in the postoperative period, the presence of primary mechanical hyperalgesia, scores of postoperative pain using a visual analog scale and plasma levels of TNF-alpha and interleukins (IL-6, IL-1β). There were no significant differences in the analysis of the variables: age, weight, duration of surgery and ASA between the two groups. The 24 hours morphine consumption in the tourniquet group compared to the control group was significantly less (p = 0.0156). The analysis of the assessment of pain intensity at rest, during coughing and deep breathing showed significantly lower VAS scores in tourniquet group compared to the control group with p = 0.0087, p = 0.0119, p = 0.0015, respectively. The presence or absence of mechanical hyperalgesia in the demarcated area near the postoperative wound was not different between groups (p = 0.0704). There were no significant differences in the levels of TNF-alpha (p = 0.0724) and IL-1β (p = 0.0532) between the two groups. There were significant differences in the dose of IL-6: between the two groups over time (p<0.0001). The remote ischemic preconditioning promoted satisfactory analgesia and reduced morphine consumption in patients undergoing conventional cholecystectomy, without, however, altering the presence of primary mechanical hyperalgesia at the site of injury or serum levels of inflammatory mediators.